Patient-derived organoids facilitating individual therapy in an adolescent with embryonal rhabdomyosarcoma of the cervix: a case report and literature review - Qiao, Xinyu; Zeng, Zhaomin; Chen, Peng; Xi, Mingrong; Hou, Minmin (Frontiers in Oncology, 2023)
Rhabdomyosarcoma (RMS) is a highly aggressive pediatric neoplasm that originates from striated muscle or undifferentiated mesenchymal cells. Based on its histopathological characteristics, the World Health Organization categorizes RMS into four distinct subtypes: embryonal RMS, alveolar RMS, pleomorphic RMS, and sclerosing/spindle cell RMS. Embryonal RMS represents the predominant subtype and primarily manifests in the head and neck region, with the genitourinary system being the subsequent most frequent site of occurrence. Embryonal rhabdomyosarcoma of the cervix (cERMS) is more insidious in the reproductive tract, and there is still a lack of consensus on its treatment. Patientderived organoids (PDOs) are being prioritized for use in guiding personalized medicine. The application of PDOs to test the sensitivity of chemotherapy drugs in patients with cERMS has rarely been reported. In this case report, we delineate the presentation and diagnosis of a 16-year-old adolescent with cERMS, emphasizing the utilization of PDOs in the management of this infrequent neoplasm. We intend to elucidate the diagnostic and therapeutic processes associated with cERMS by referencing previously reported literature on this infrequent tumor, aiming to offer a foundation for clinical practice.